La documentación latina del rey Alfonso VI y la Biblia: identificación de citas en el preambulum y motivos bíblicos en la sanctio - Martínez Ortega, Ricardo (1999)
This paper deals with two aspects of the latin documents of king Alphonse VI, recently published: the identification and study of the Biblical quotations in the preambulum and the analysis of the Biblical motifs in the sanctio, through which different questions are explained, such as the verse «et tiranni terram possident», the term «marenata» and the name «Zabulo», that is equal here to «diabolus».
Keywords: Alfonso -- VI, -- Rey de León; Biblia; Documentación; Lengua latina